Análisis jurídico y dogmático del agente encubierto en el código orgánico integral penal - Hernández Zambrano, Luis Víctor (2020)
Not only in Ecuador, but also internationally, it has been argued that it is necessary to grant exceptional investigative powers to properly and properly deal with organized crime and various other serious crimes, such as illegal drug trafficking, "money laundering", terrorism, human trafficking, corruption, prostitution and child pornography. The Undercover Agent is one of the special investigative techniques, as they are called by the United Nations Convention against Transnational Organized Crime of 2000, and are absolutely essential tools for the criminal investigation of illegal acts of especially complex commission; they must and deserve to be adequately regulated in the legal systems of each country, in accordance with their constitutional and legal principles; and they must be used in a highly professional manner, and respectful and guarantee of due criminal proceedings........